Internalisasi Nilai-Nilai Moderasi Beragama Pada Madrasah Aliyah Negeri di Kalimantan Timur - Habib Anwar Al-Anshori; Babun Suharto; Mukhamad Ilyasin (LP3M STITNU AL HIKMAH MOJOKERTO, 2022)
Internalization of the Values ​​of Religious Moderation at State Madrasah Aliyah in East Kalimantan which has the distinction of inculcating an understanding of religious moderation in students is very necessary so that students have a broad understanding of diversity and religion. The purpose of this study is to identify and explore the Transformation of Religious Moderation values ​​at Madrasah Aliyah Negeri in East Kalimantan. The method in this research is descriptive qualitative, multi-site research type and uses a phenomenological study approach. Then the data obtained through interviews, observations and document studies. The findings of this research are the transformation of religious values ​​to foster religious moderation through new student orientation activities, learning, extracurricular activities. The implication of this research is the internalization of moderate Islamic values ​​in fostering or strengthening religious moderation as an effort to form conceptually and empirically tested moderate students.